Comparing the Influence of Green Credit on Commercial Bank Profitability in China and Abroad: Empirical Test Based on a Dynamic Panel System Using GMM - Xiaoling Song; Xin Deng; Ruixue Wu (International Journal of Financial Studies, 2019)
This study establishes a dynamic panel model for 12 Chinese-listed commercial banks and seven international commercial banks. More specifically, it examines the impact of green credit on the profitability of commercial banks and the differences between China and other countries while using the generalized method of moments. The research shows that the Equatorial Principles project-financing ratio of international banks positively affects bank profitability, while the ratio of green credit for Chinese commercial banks is inversely related to their profitability. Further, a comparative study of China and other countries highlights that the green credit business is at significantly different stages in China and the rest of the world. This study also finds that the profitability of China’s banking sector is positively affected by asset size, management expense ratio, cash ratio, and GDP growth rate, in addition to the common influencing factor of non-performing loan ratio, whereas asset size and capital adequacy ratio negatively affects the international banking sector. Drawing on these empirical conclusions, this study offers suggestions for the further development of green credit in Chinese commercial banks.